Transformational Leadership Training: A Key Driver to Improve the Effectiveness and Productivity of CV Ning Sri Stone Crusher - UDIN, UDIN; SUUD, FITRIAH M.; FIRDAUSI, AZZUHRATUL KHAIRA (The journal of contemporary issues in business and government, 2021)
CV Ning Sri is an Indonesian private company whose management activities are entirely under the family managerial. This company is engaged in stone crusher. Some main obstacles are often experienced and even have not been resolved properly by the stone crusher company of CV Ning Sri, namely (a) the weak managerial and leadership system, where the leader places more emphasis on the transactional element to all employees in completing their task; (b) the intensity of employee turnover is too high, which makes it difficult to identify and retain talented employees; (c) the frequent occurrence of non-ethical behavior of employees in the form of tardiness and theft in the workplace. Therefore, based on these various problems, in today's highly competitive free market era, transformational leadership is very important to be realized in order to improve effectiveness and performance among employees and managers, as well as the CV Ning Sri company as a whole. In addition, transformational leadership has been considered essential for creating superior performance and organizational effectiveness.